E-agriculture of hydroponic farming with nutrient film technique (NFT) using internet of thing - Suheri Agus; Widaningsih Sri; Awalia Uniq Fadilah (BIO Web of Conferences)
Agriculture is one of the activities to produce food. Nowadays, farming is not only done on the ground on open land but can be done with the hydroponic method. Hydroponic technique is a technique of planting with water media that is given nutrients. One of the hydroponic techniques is Nutrient Film Technique. A key challenge in hydroponic farming is the continuous monitoring of environmental factors that affect plant growth. This will make it difficult for farmers because it is very dependent on human labor, especially large-scale hydroponic gardens. Therefore, hydroponic plant management requires a monitoring system that can help hydroponic farmers in their cultivation. This research develops an automated monitoring system using Internet of Things (IoT) technology to track temperature, light intensity, humidity, and water usage. This system aims to reduce manual labor and optimize plant growth conditions. If there are conditions that are not ideal, the system can give feedback to drive actuators such as fans, lights and water pumps. The devices used are sensors, arduino microcontroller, wifi modules and internet networks. The research employs a prototype model, utilizing UML for system design. The backend is developed using PHP with the Laravel framework, while MySQL is used for database management. The system is anticipated to enhance efficiency in hydroponic farming by automating environmental monitoring and control, thereby reducing reliance on manual labor and improving plant growth conditions. Additionally, the system features CCTV camera monitoring for real-time observation, as well as tools for generating harvest reports, tool usage reports, and nutritional data.